P-069 A SINGLE CENTRE RETROSPECTIVE 14 YEAR REVIEW OF PATIENT OUTCOMES FOLLOWING IPOM LAPAROSCOPIC VENTRAL HERNIA REPAIR WITH PVDF MESH. (13th October 2022) - Byrne, H; Ansong, E; Abdul-Kaliq, A; Finch, G
Abstract: Aim: Laparoscopic ventral hernia repair (LVHR) is a widely accepted minimally invasive technique. However, there remains debate regarding appropriate patient selection, the type of mesh used and for what size and type of defect. We aimed to review our experience of IPOM LVHR using PVDF mesh and compare our outcomes to the current literature. Material and Methods: Operative records identified all patients who had undergone an IPOM LVHR with PVDF mesh from 2007–2021. The type, number and size of hernial defects, the sac contents, along with the size of mesh used and the type of fixation was collated. Length of stay (LoS), as well as early and late post-operative complications were also analyzed. Results: A total of 287 patients are included in the study to date. 32.3% of patients were categorised within Obese Class II or III (BMI 35 – >40). Major early and late complications were observed in 4.6% and 3.1% of cases respectively. An 8.7% recurrence rate was observed. 87% of recurrences had an original defect classed as large (>4cm), with a median BMI of 30.5. Conclusion: In conclusion, our post-operative outcomes are in keeping with those reported in the literature. In our experience, a high BMI does not preclude patients from undergoing a LVHR and having a good result. Debates are ongoing with regards to the timing and indication for LVHR in the obese and our results are encouraging, especially considering current national statistics estimate approximately 30% of the UK population are classed as obese.